Photocatalytic degradation of tetracycline antibiotic by a novel Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction: Performance, mechanism insight and toxicity assessment - Li, Shijie; Wang, Chunchun; Liu, Yanping; Cai, Mingjie; Wang, Yaning; Zhang, Huiqiu; Guo, Yang; Zhao, Wei; Wang, Zhaohui; Chen, Xiaobo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •0D/3D Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction was constructed.•The heterojunction exhibited excellent photocatalytic performance for antibiotics.•A plausible degradation pathway for TC was proposed.•S-scheme heterojunction largely boosted charge separation and ROS production. The fabrication of step-scheme (S-scheme) heterojunction with superior redox capability has been emerging as a prospective strategy for environmental remediation. Herein, novel Bi2Sn2O7/Bi2MoO6 S-scheme heterojunctions have been fabricated via in-situ anchoring Bi2Sn2O7 nanoparticles on Bi2MoO6 microspheres. The optimized Bi2Sn2O7/Bi2MoO6 (BSO/BMO-6%) attains the highest reaction rate constant (k) in the degradation of tetracycline hydrochloride (TC, k = 0.0397 min−1), which is 3.62 folds higher than that of pristine Bi2MoO6. Such an improvement is originated from more exposed active sites, higher photo-excited charge separation efficiency, superior redox ability, and efficient production of reactive h+, •OH and •O2–. Besides, Bi2Sn2O7/Bi2MoO6 could efficiently degrade the TC antibiotic in actual water matrix. Significantly, the toxicity evaluation verifies the nontoxicity of Bi2Sn2O7/Bi2MoO6. Moreover, the degradation pathways of TC are determined and the toxicity of degradation intermediates is appraised by using HPLC-MS spectra and QSAR prediction. A possible photocatalytic mechanism over S-scheme Bi2Sn2O7/Bi2MoO6 has been elucidated based on experimental studies combined with density functional theory (DFT) calculations. This work offers new insights for the design of high-performance S-scheme heterojunctions for environmental remediation.